Glibenclamide Reduces Primary Human Monocyte Functions Against Tuberculosis Infection by Enhancing M2 Polarization - Kewcharoenwong, Chidchamai; Prabowo, Satria A.; Bancroft, Gregory J.; Fletcher, Helen A.; Lertmemongkolchai, Ganjana (Frontiers in Immunology, 2018)
Tuberculosis (TB) is a global public health problem, which is caused by Mycobacterium tuberculosis (Mtb). Type 2 diabetes mellitus (T2DM) is one of the leading predisposing factors for development of TB after HIV/AIDS. Glibenclamide is a widely used anti-diabetic drug in low and middle-income countries where the incidence of tuberculosis is very high. In a human macrophage cell line, glibenclamide, a K+ATP-channel blocker, promoted alternative activation of macrophages by enhancing expression of the M2 marker CD206 during M2 polarization. M2 macrophages are considered poorly microbicidal and associated with TB susceptibility. Here, we investigated the effect of glibenclamide on M1 and M2 phenotypes of primary human monocytes and further determined whether specific drug treatment for T2DM individuals influences the antibacterial function of monocytes in response to mycobacterial infection. We found that glibenclamide significantly reduced M1 (HLA-DR+ and CD86+) surface markers and TNF-α production on primary human monocytes against mycobacterial infection. In contrast, M2 (CD163+ and CD206+) surface markers and IL-10 production were enhanced by pretreatment with glibenclamide. Additionally, reduction of bactericidal activity also occurred when primary human monocytes from T2DM individuals who were being treated with glibenclamide were infected with Mtb in vitro, consistent with the cytokine responses. We conclude that glibenclamide reduces M1 and promotes M2 polarization leading to impaired bactericidal ability of primary human monocytes of T2DM individuals in response to Mtb and may lead to increased susceptibility of T2DM individuals to TB and other bacterial infectious diseases.